The experimental pragmatics: A review of language constructing and interpreting - Ghafar, Zanyar Nathir (Yayasan Mitra Persada Nusantara, 2023)
In the field of empirical pragmatics, a significant amount of research is focused on testing empirical hypotheses derived from the study of linguistic and intellectual pragmatics. Most of this study is centered on analyzing the components of conveyed meaning that Information is